Blue light cystoscopy- as an improvised diagnostic modality for bladder tumours - Mushtaq, Rabeea; Saba Samad; Areeba Raza; Aiman Riaz; Hamna Naseem; Naseha Mushtaq (Journal of the Pakistan Medical Association, 2024)
Bladder cancer remains a significant global health concern, being the 10th most common malignancy worldwide and the 6th most common neoplasia in males, with alarming annual incidence and mortality rates. The current narrative review was planned to delve into the multifaceted landscape of bladder cancer, exploring its epidemiology, risk factors and diagnostic modalities. While white light cystoscopy has long been considered the gold standard for bladder cancer diagnosis and surveillance, the emergence of blue light cystoscopy has ushered in a new era of early detection. Numerous studies have demonstrated BLC's superiority in reducing the risk of progression and recurrence of this lethal cancer. However, the widespread adoption of this technology remains elusive. Recent advancements in diagnostic procedures have revolutionised imaging modalities, with blue light cystoscopy and narrow-band imaging emerging as promising replacements for white light cystoscopy. Clinical trials have underscored the superior performance of blue light cystoscopy over white light cystoscopy, with reduced recurrence and progression rates. For non-muscle invasive bladder cancer, Bacillus Calmette-Guérin immunotherapy remains the gold standard adjuvant therapy, while cystectomy is considered for cases resistant to Bacillus Calmette-Guérin or with a high risk of progression. Transurethral resection of bladder tumour followed by intravesical chemotherapy is a key intervention for early-stage bladder cancer. Blue light cystoscopy is poised to overcome the limitations of white light cystoscopy by providing comprehensive visualisation of neoplastic boundaries, particularly benefiting late-detected squamous-type non-muscle invasive urothelial carcinomas associated with lower survival rates. The current findings highlighted the transformative potential of blue light cystoscopy and other emerging diagnostic techniques, offering a ray of hope in the battle against bladder cancer, while emphasising the need for wider adoption and integration into clinical practice. Key Words: Bladder carcinoma, Blue light cystoscopy, White light cystoscopy, Urothelial carcinoma, Non-muscle invasive carcinoma, Narrow-band imaging.